2018
DOI: 10.1016/j.jacc.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Malignant Ventricular Arrhythmic Substrate in Patients With Brugada Syndrome

Abstract: In Brugada syndrome dynamic substrate variability represents the pathophysiological basis of lethal ventricular tachyarrhythmias. Substrate size is independently associated with arrhythmia inducibility, and its determination after ajmaline identifies high-risk patients missed by clinical criteria. Substrate ablation is associated with electrocardiogram normalization and not arrhythmia reinducibility. (Epicardial Ablation in Brugada Syndrome [BRUGADA_I]; NCT02641431; Epicardial Ablation in Brugada Syndrome: An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 25 publications
1
59
0
1
Order By: Relevance
“…It is interesting that, again, none of the SNPs studied, including that in the SCN5A gene, were found to be predisposing to syncope, atrial fibrillation, or total mortality. However, again, the electrocardiographic data may be misleading, as in the prior study, because it relies on spontaneously collected electrocardiograms, which are well known to be unreliable in the diagnosis of BrS, even for about 80% of patients who have experienced cardiac arrest or syncope because of documented ventricular fibrillation [5,26]. A study by a different group [27] studying the same genetic variation (rs9388451) adjacent to the HEY2 gene reported its role in the alteration of ion channel expression across the cardiac ventricular wall and its possible association with BrS.…”
Section: The Challenges Surrounding Brs Geneticsmentioning
confidence: 88%
“…It is interesting that, again, none of the SNPs studied, including that in the SCN5A gene, were found to be predisposing to syncope, atrial fibrillation, or total mortality. However, again, the electrocardiographic data may be misleading, as in the prior study, because it relies on spontaneously collected electrocardiograms, which are well known to be unreliable in the diagnosis of BrS, even for about 80% of patients who have experienced cardiac arrest or syncope because of documented ventricular fibrillation [5,26]. A study by a different group [27] studying the same genetic variation (rs9388451) adjacent to the HEY2 gene reported its role in the alteration of ion channel expression across the cardiac ventricular wall and its possible association with BrS.…”
Section: The Challenges Surrounding Brs Geneticsmentioning
confidence: 88%
“…In the 2017 AHA/ACC/HRS guideline for ventricular arrhythmias and SCD, an EPS with programmed ventricular stimulation using single or double extrastimuli may be considered for further risk stratification in asymptomatic and spontaneous type 1patients (Kusumoto et al, 2017 ). Newly studies suggested that extent of substrate is the only independent predictor of inducibility of VT or VF and may contribute to a new marker for risk stratification and therapy (Pappone et al, 2018 ). The differences of sex-related cardiac electrophysiological characteristics may be the main reason contributing to the result, that women have lower expression of KChIP2 which is the main accessory subunit of transient outward current in right ventricular epicardium (Tadros et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is remarkable because, in view of the risks involved (see below) and perceived lack of diagnostic added‐value, this test is generally considered contraindicated for patients who already have documentation of a type‐I Brugada pattern on a resting ECG 7. That “orthodox” view of the test, however, is evolving: SCB tests have been performed in patients with documentation of a type‐I pattern during fever8 or to better delineate the arrhythmogenic substrate during radiofrequency ablation 9…”
Section: The Present Study: a Shift From Diagnostic To Prognostic Test?mentioning
confidence: 99%
“…Patients diagnosed with Brugada syndrome who are then left untreated may develop unbearable anxiety that could lead to therapeutic interventions with limited proof of benefit 22. In a recent study,9 84 asymptomatic patients with only drug‐induced type‐I ECG first underwent a prophylactic implantable cardioverter defibrillator implantation and, after remaining free of arrhythmias for an undisclosed time period, underwent prophylactic epicardial ablation of extensive areas of their right ventricle. If the second explanation for the type‐I paradox is correct, it is possible that some of the patients undergoing these 2 invasive procedures do not even have the disease we call Brugada syndrome.…”
Section: Asymptomatic Patients Without a Spontaneous Type‐imentioning
confidence: 99%
See 1 more Smart Citation